Exploring local vs global brand associations in an emerging market using BCM technique - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - The purpose of this paper is to differentiate local versus global brand associations in an emerging market (Turkey)'s coffee shop market. Design/methodology/approach - Two leading coffee shop brands - one local and one global - were analyzed with an emerging exploratory research technique - brand concept mapping (BCM) - to reveal their strong, favorable and unique associations leading them to market leadership. Findings - The results indicate that, these two successful brands both have distinctive, yet relevant positions in their consumers' mind. Local cultural experience is relevant for differentiating local brands, even if the coffee shop concept is globally imported. Global coffee shop brand, on the other hand, means membership to global middle income segment and is remembered as global fast coffee service. Research limitations/implications - The main limitation of this exploratory study is the sample size limitation by its nature. So, the generalizability of the results should be approached with caution. Researchers use BCM technique; however, this method does not permit to reveal the expected levels and the importance of the attributes. Thus, further research are suggested to be complementary. Originality/value - This study fills the research gap in revealing and comparing local vs global brand associations by using BCM technique, which enables one to measure the strength, unique and favorable associations/brand images more suitable to Keller's (1993) conceptualization. This study pioneers in using this technique in international branding.
Keywords: Emerging markets; Brand image; International marketing; Brand associations; Brand concept map; COUNTRY-OF-ORIGIN; CONCEPT MAPS; CONSUMER; STRATEGIES; EQUITY; CREDIBILITY; ATTITUDES; CUSTOMER; PRODUCT; CULTURE